Hubungan antara Gigi Berjejal dan Status Gizi pada Remaja - Andries, Agnes M.; Anindita, Pritartha S.; Gunawan, Paulina N. (Universitas Sam Ratulangi, 2021)
Abstract: Malocclusion is one of the most common dental and oral health problems after caries and periodontal disease. Most of the malocclusions occur in adolescence and manifest as crowding teeth. Malnutrition can inhibit the growth and development of the skull and jaw bones, therefore, the permanent teeth have lack space to erupt resulting in crowding teeth. This study was aimed to determine the relationship between crowding teeth and nutritional status among adolescents in Indonesia. This was a literature review study using three databases, Google Scholar, GARUDA, and Pubmed. Keywords used were crowding, malocclusion, malnutrition, adolescent, Height for Index, BMI, nutritional status, adolescents. After being selected based on inclusion and exclusion criteria, a critical appraisal was carried out and obtained 8 cross-sectional study literatures. The review showed that there were more literatures stating that there was no relationship between crowding teeth and nutritional status among adolescents. Apart from nutritional status, there were several other factors that could affect crowding teeth in adolescents such as bad habits, history of crowding deciduous teeth, heredity, and socioeconomic status. In conclusion, crowding teeth in adolescents is influenced by nutritional status as well as other factorsKeywords: crowding, nutritional status, adolescents.Â Abstrak: Maloklusi telah menjadi salah satu permasalahan kesehatan gigi dan mulut yang sering dijumpai setelah karies dan penyakit periodontal. Sebagian besar maloklusi terjadi pada usia remaja dalam bentuk gigi berjejal. Status gizi yang kurang dapat menghambat pertumbuhan dan perkembangan tulang tengkorak maupun rahang yang menyebabkan gigi permanen kekurangan ruang untuk erupsi dan terjadi gigi berjejal. Penelitian ini bertujuan untuk mengetahui hubungan gigi berjejal dan status gizi pada remaja di Indonesia. Jenis penelitian ialah literature review dengan pencarian data menggunakan tiga database yaitu Google Scholar, GARUDA, dan Pubmed. Kata kunci yang digunakan yaitu crowding, malocclusion, malnutrition, BMI, adolescent, maloklusi, TB/U, IMT, Status Gizi, Remaja. Setelah diseleksi berdasarkan kriteria inklusi dan ekslusi, dilakukan critical appraisal dan didapatkan 8 literatur cross-sectional study. Hasil kajian menunjukkan terdapat lebih banyak literatur yang menyatakan tidak terdapat hubungan antara gigi berjejal dan status gizi pada remaja. Selain status gizi, faktor lainnya yang dapat memengaruhi terjadinya gigi berjejal pada remaja ialah kebiasaan buruk, riwayat gigi desidui berjejal, keturunan, dan status sosial ekonomi orang tua.. Simpulan penelitian ini ialah gigi berjejal pada remaja tidak hanya dipengaruhi oleh status gizi saja namun dapat disebabkan oleh faktor lain juga.Kata kunci: gigi berjejal, status gizi, remaja